Implications of the COVID-19 Pandemic on the Family Structural Dimensions: A Correlational Study - Margarida Silva; Manuela Ferreira; Helena Loureiro; Teresa Kraus; Angelica Santos; Maria Henriqueta Figueiredo (MDPI AG, 2023)
The COVID-19 pandemic caused changes in the families' social support network, employment status, and family income, which are the focus of attention of family health nurses. This study aims to describe the pandemic's repercussions in the areas of attention of the structural dimension of families according to the Dynamic Model of Family Assessment and Intervention, as perceived by Portuguese families, and to relate the changes in their employment status according to the variables of the structural dimension. A quantitative, descriptive, and correlational study was conducted using snowball sampling. A questionnaire of sociodemographic characterization and assessment of the family structural dimension according to the model's operational matrix was applied to 235 family members. Changes were found in their employment status; family income; intensity and frequency of contact with family, friends, and coworkers; frequency of contact with educational/health/religious institutions and community groups; cultural activities; and housing comfort conditions such as the use of heating/air conditioning, gas, and water consumption. Changes in employment status were related to family income, interaction with friends, frequency of cultural activities, and use of air conditioning and heating. Knowing the implications of the pandemic on the family's structural dimension results in a nursing intervention more focused on family needs.